(untitled) (Materiali di Estetica. Terza serie, 2020)
Writing is a search for and a construction of situations: more than a pre-existing project, a resulting map of the language, of the athmosphere in which it takes place. The landscape is the form of this map, meaning by it a conceptual construction that develops both outside and inside man. This landscape is a soundscape, where can be found the imprint of overlapping voices (the stratifications of the langues reçues and the intersections of speech, the musical traces and the literary palimpsests). On their basis I try to construct an image of experience as a crossing, in which metrics as a cognitive rule and score to be shared acts as a meeting ground, as a framing.